A prospective case–control study of non‐healing wounds of the lower limbs – the value of biopsies for ulcerating carcinoma. (22nd May 2014) - Gil, T.; Pistunovich, Y.; Kulikovsky, M.; Elmalah, I.; Krausz, Y.; Mettanes, I.; Lavi, I.; Har‐shai, Y.
Abstract: Background: In some leg ulcer patients there is cancer that is responsible for lack of healing of such a wound. Aim: This study was aimed at prospective analysis of histopathology of non‐healing wounds (NHWs) in the patient presenting with high and low suspicion for ulcerating carcinoma. Material and methods: Forty patients with NHWs were enrolled and had been prospectively divided into two groups: 25 patients with high suspicion for ulcerating carcinoma according to their medical history and physical examination, and the second group of 15 patients without suspicion for malignancy (control group). All NHWs were photographed and underwent biopsies. Results: In the control group biopsies did not reveal cancers. On the contrary, in 10 patients (40%) from high suspicion group biopsies revealed cancers: seven basal cell carcinomas (BCCs), one – malignant melanoma, one – Bowen's disease and one – squamous cell carcinomas. Histopathology of six of seven BCCs suggested that non‐healing benign wound might have preceded malignancy. We found that leg ulcers which were small (wound area less than 3 cm 2 ), longstanding (duration 24 ≤ weeks), presenting with granulation tissue covering ≥75% of the wound area, with a dull pink appearance of the granulation tissue, or an atypical clinical presentation, can actually be an ulcerating carcinoma. Dull pink granulation tissue or an atypical clinical presentation of ulceration, as a single clinical finding, suggested an underlying malignancy with a statistical significance (71.5% vs. 0%; P = 0.001 and 27.8% vs. 0%; P = 0.0049 respectively). Conclusions: Prevalence of malignancy, primarily: BCCs in NHWs, may be higher than expected and clinical features suggestive of such a nature of ulcer are an indication for diagnostic biopsy.